Treatments in veterinary homeopathy - Romeo T. Cristina (Medicamentul Veterinar)
The paper is a small guide about: what is to know, being a vet, related to homeopathic therapy institution (anamnesys and clinical examination, what are the polichrests), antagonisms and synergisms, data about somehomeopathic conditionings as well the doses and way of administration choosing.